Effect of UV Laser Radiation on “Positive Regulation of Telomere Maintenance” in Saccharomyces cerevisiae: Effect of UV Laser on “Positive Regulation of Telomere Maintenance - Rezaei-Tavirani, Mostafa; Arjmand, Babak; Safari-Alighiarloo, Nahid; Razzaghi, Mohammad Reza; Rostami-Nejad, Mohammad; Rezaei-Tavirani, Majid; Mansouri, Vahid; Vafaee, Reza (Journal of Lasers in Medical Sciences, 2021)
Introduction: Excessive exposure to ultraviolet (UV) radiation may cause a variety of skin cancers and damage to the eye lens. The assessment of different aspects of UV damage has attracted researchers’ interest. UV radiation to simple biological models such as Saccharomyces cerevisiae of yeast family could help to find out different molecular changes resulting from radiation. The assessment and network analysis of gene expression data about yeast cells radiated by the UV laser was the aim of this study. Methods: The gene expression profiles of S. cerevisiae samples in the presence of the UV laser at 30 seconds radiation and 15 minutes’ post-radiation time are compared with the control profiles. The significantly expressed genes interacted and the central nodes and related biological terms were identified. Results: The main connected component of the network including 427 nodes was analyzed and 11 central differentially expressed genes (DEGs) were determined. RPN11, UBI4, HSP82, and HSC82 as critical DEGs and “positive regulation of telomere maintenance” as a related biological term was introduced. Conclusion: The finding has provided a new perspective on laser application in the rejuvenation process. It seems that the laser can be used as a suitable agent against the aging process which is a limiting factor in human life. DOI:10.34172/jlms.2021.87